2017
DOI: 10.18203/2394-6040.ijcmph20173329
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological surveillance of tuberculosis among HIV/AIDS seropositive individuals attending ART center at a tertiary care teaching hospital

Abstract: Background:HIBackground: HIV/ AIDS is an epidemic that is most prevalent in India affecting people of different age groups, occupations and gender. It has a severe impact on the health status of the affected individuals. With the increase in the transmission of HIV there is also an increase in the existence of TB as a co-infection. In this context, the aim of our study is to emphasize the factors affecting the occurrence, transmission and prognosis of HIV/AIDS patients along with TB co-infection.Methods: A cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…This finding was comparatively lower than a study conducted in different areas of Ethiopia like Amhara region Northwest Ethiopia 27.7%, 27 to a study conducted among 12,980 Ethiopian study participants 25.59%, 38 to a study that was done in Bahir Dar Flege Hiwot specialized hospital 10.1%, 39 a facility-based retrospective study conducted at Hawassa University referral hospital of Ethiopia reported that 18.2%, 40 another cross-sectional study (n=1153) that was done at private health institutions in Ethiopia 20%, 41 and a retrospective study at Butajira Zonal hospital, Ethiopia that founds 20.3%. 9 Not only from local studies but also abroad studies have shown that the higher magnitude of PTB among HIVpositive individuals including from South India 60.58%, 42 Nigeria 42.3%, 43 Tanzania (11.0%) participants developed TB while receiving ART, 37 and the prevalence rate of TB while receiving ART from South Africa reported 10%. 44 The discrepancy in the magnitude of TB among HIVpositive participants may be explained by the difference in the health-care system among ART centres, variation in study design, 45 the diagnostic methods 46 employed (smear microscopy, culture, GeneXpert), ART regimens and its adherence 47 and adverse drug-related problems that trigger MTB-MDR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding was comparatively lower than a study conducted in different areas of Ethiopia like Amhara region Northwest Ethiopia 27.7%, 27 to a study conducted among 12,980 Ethiopian study participants 25.59%, 38 to a study that was done in Bahir Dar Flege Hiwot specialized hospital 10.1%, 39 a facility-based retrospective study conducted at Hawassa University referral hospital of Ethiopia reported that 18.2%, 40 another cross-sectional study (n=1153) that was done at private health institutions in Ethiopia 20%, 41 and a retrospective study at Butajira Zonal hospital, Ethiopia that founds 20.3%. 9 Not only from local studies but also abroad studies have shown that the higher magnitude of PTB among HIVpositive individuals including from South India 60.58%, 42 Nigeria 42.3%, 43 Tanzania (11.0%) participants developed TB while receiving ART, 37 and the prevalence rate of TB while receiving ART from South Africa reported 10%. 44 The discrepancy in the magnitude of TB among HIVpositive participants may be explained by the difference in the health-care system among ART centres, variation in study design, 45 the diagnostic methods 46 employed (smear microscopy, culture, GeneXpert), ART regimens and its adherence 47 and adverse drug-related problems that trigger MTB-MDR.…”
Section: Discussionmentioning
confidence: 99%
“…Not only from local studies but also abroad studies have shown that the higher magnitude of PTB among HIV-positive individuals including from South India 60.58%, 42 Nigeria 42.3%, 43 Tanzania (11.0%) participants developed TB while receiving ART, 37 and the prevalence rate of TB while receiving ART from South Africa reported 10%. 44 The discrepancy in the magnitude of TB among HIV-positive participants may be explained by the difference in the health-care system among ART centres, variation in study design, 45 the diagnostic methods 46 employed (smear microscopy, culture, GeneXpert), ART regimens and its adherence 47 and adverse drug-related problems that trigger MTB-MDR.…”
Section: Discussionmentioning
confidence: 99%